Seizures and epilepsy in patients with ischaemic stroke. - Zöllner, Johann Philipp; Schmitt, Friedhelm C.; Rosenow, Felix; Kohlhase, Konstantin; Seiler, Alexander; Strzelczyk, Adam; Stefan, Hermann (Neurological Research and Practice, 2021)
BACKGROUND: With the increased efficacy of stroke treatments, diagnosis and specific treatment needs of patients with post-stroke seizures (PSS) and post-stroke epilepsy have become increasingly important. PSS can complicate the diagnosis of a stroke and the treatment of stroke patients, and can worsen post-stroke morbidity. This narrative review considers current treatment guidelines, the specifics of antiseizure treatment in stroke patients as well as the state-of-the-art in clinical and imaging research of post-stroke epilepsy. Treatment of PSS needs to consider indications for antiseizure medication treatment as well as individual clinical and social factors. Furthermore, potential interactions between stroke and antiseizure treatments must be carefully considered. The relationship between acute recanalizing stroke therapy (intravenous thrombolysis and mechanical thrombectomy) and the emergence of PSS is currently the subject of an intensive discussion. In the subacute and chronic post-stroke phases, important specific interactions between necessary antiseizure and stroke treatments (anticoagulation, cardiac medication) need to be considered. Among all forms of prevention, primary prevention is currently the most intensively researched. This includes specifically the repurposing of drugs that were not originally developed for antiseizure properties, such as statins. PSS are presently the subject of extensive basic clinical research. Of specific interest are the role of post-stroke excitotoxicity and blood-brain barrier disruption for the emergence of PSS in the acute symptomatic as well as late (> 1 week after the stroke) periods. Current magnetic resonance imaging research focussing on glutamate excitotoxicity as well as diffusion-based estimation of blood-brain barrier integrity aim to elucidate the pathophysiology of seizures after stroke and the principles of epileptogenesis in structural epilepsy in general. These approaches may also reveal new imaging-based biomarkers for prediction of PSS and post-stroke epilepsy. CONCLUSION: PSS require the performance of individual risk assessments, accounting for the potential effectiveness and side effects of antiseizure therapy. The use of intravenous thrombolysis and mechanical thrombectomy is not associated with an increased risk of PSS. Advances in stroke imaging may reveal biomarkers for PSS.
EVALuna2:527488